PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP HASIL BELAJAR PADA MATA PELAJARAN FIQIH DI KELAS V MI DARUL ULUM CIMAHPAR BOGOR - Raden Sri Nurhayati; Oking Setia Priatna; M. Dahlan R. (Yayasan Akrab Pekanbaru, 2019)
Teaching and learning activities that give birth to the interaction of human elements are a process in order to achieve teaching goals. The formulation of the problem in this study is whether there is an effect of giving reward and punishment to the learning outcomes in Fiqh subjects in the fifth grade of MI Darul Ulum Cimahpar Bogor? The approach of this research is a quantitative approach. Data collection techniques in this study are questionnaires, documentation and observation. The sample in the study was the fifth grade students of MI Darul Ulum Cimahpar Bogor, amounting to 22 students. Based on the calculation results, it can be concluded that there is an effect of giving reward and punishment to the learning outcomes in Fiqh subjects. This is indicated by the output of the pearson correlation value between the variable reward and punishment on the learning outcomes of Class V students of MI Darul Ulum Cimahpar Bogor at 0.713 **. While the closeness of the relationship is strong because it is in the range of 0.60-0.799.